THE DYNAMICS OF INDIVIDUAL ENTREPRENEURIAL ORIENTATION IN THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL INTENTION - Efrata, Tommy C.; Radianto, Wirawan E. D.; Effendy, Junko A. (Universitas Brawijaya, Indonesia, 2021)
Studies on individual entrepreneurial orientation as well as the relationship between innovativeness, proactiveness, and risk-taking have not received much attention in the entrepreneurship literature. Therefore, this study aims to explore the relationship between the components of individual entrepreneurial orientation and examine the relationship between entrepreneurship education, individual entrepreneurial orientation, and entrepreneurial intention. The model developed was tested on 231 management and business students who have completed an entrepreneurship education program in the university. The data obtained were processed using PLS-SEM statistical programming to evaluate the outer and inner structure of the model. This study indicates that most of the arguments of the model compilers as explicitly observed in determining the effect of proactiveness on innovation have been confirmed. At the same time, risk-taking was discovered not to affect personal innovativeness. Entrepreneurship education was also proven to have affected individual entrepreneurial orientation, while only innovativeness and risk-taking were confirmed to have the ability to increase entrepreneurial intention. The findings succeeded in filling the void related to the study on the relationship dynamics between the dimensions forming individual entrepreneurial orientation. They also comprehensively complement the study model designed in the scope of individual entrepreneurial orientation, which was partially completed. Therefore, the results are expected to provide direction for educators and scholars in the area of entrepreneurship.